Inhibition of dsRNA-induced signaling in hepatitis C virus-infected cells by NS3 protease-dependent and -independent mechanisms - Guofeng Cheng; Jin Zhong; Francis V. Chisari (2006)
The recent establishment of a robust hepatitis C virus (HCV) cell culture system permits analysis of virus-host interactions during HCV infection. Here, we report that HCV genotype 2a (JFH-1) infection fails to induce IFN-beta or IFN-stimulated gene expression in Huh-7 cells, and that it blocks IFN-beta and IFN-stimulated gene production after transfection of synthetic dsRNA. Overexpression of individual components of the dsRNA-signaling pathway in HCV-infected and uninfected cells indicates that HCV inhibits IFN-beta promoter activity by inactivating the mitochondrial antiviral signaling protein/IFN-beta promoter stimulator 1 (MAVS/IPS-1), while leaving the IFN-induced Janus kinases-signal transducers and activators of transcription (JAK-STAT) signaling pathway intact. We also show that MAVS/IPS-1-dependent IFN-beta promoter activity in HCV-infected cells is fully restored by the nonstructural protein 3 (NS3) protease inhibitor BILN2061. In contrast, synthetic dsRNA-induced IFN-beta promoter activity is not restored by BILN2061, although it is partially restored by overexpression of RIG-I. These results support recently reported evidence that the HCV NS3 protease blunts the ability of HCV to induce IFN-beta promoter activity by proteolytically cleaving MAVS/IPS-1. The results also suggest that HCV blocks the synthetic dsRNA-induced signaling pathway at a point upstream of MAVS/IPS-1, and that it does so by an NS3-independent mechanism.